Dva nova taksona v slovenski favni metuljev (Lepidoptera) - Gomboc, Stanislav (Acta entomologica slovenica (Ljubljana), 1999)
In NE Slovenia (Subpannonian region), by means of light traps, we verified two new species of Slovenian Lepidoptera fauna: Scopula corrivalaria (Kretschmar, 1862) (Geometridae) - 1 specimen and Phragmatiphila nexa (Hübner, 1808) (Noctuidae) - 4 specimens. Both species have been verified at the same locality in hydrophilic forest - Alnetum , Črni Log near Mala Polana, at an altitude of 166 m, UTM=XM06. Due to their narrow area these species could become endangered if we interfere with their natural environment.
Keywords: entomologija; Lepidoptera; metulji; Slovenia; Slovenija